(untitled) (Research, Society and Development, 2022)
The American Tegumentary Leishmaniasis (ATL) is an infeccious, non-contagious disease caused by protozoa of the genus Leishmania. It is considerated a neglected disease which mainly affects vulnerable people in a socioeconomic point of view. On this basis, this study aimed to analyse the sociodemographic and clinical profile of the ATL cases in the state of Pará. This is a retrospective, descriptive and cross-sectional study with a quantitative approach of cases of American Tegumentary Leishmaniasis in the state of Pará between 2010 and 2019. The data were obtained from the Sistema Nacional de Agravos de Notificação (SINAN), in Departamento de Informática do Sistema Único de Saúde (DATASUS). Thus, within the stipulated period, 32.412 cases of Cutaneous Leishmaniasis were reported in Pará. Among the most affected individuals there are males (80.95%; n=26,238), age 20-39 years old (49.69%) and incomplete elementary school (54.27%; n=17,590). Related to the clinical evolution, 74,27% (n=24.072) of the pacients evolved to cure. These results indicate that the state of Pará is endemic for ATL and it affects mainly adults who work in forest regions and people without knowledgment about the disease due to low scolarity, making them more vulnerable. Therefore, these data are essencial for a better knowledgement of the disease in the state of Pará, it helps the control of the ATL by the epidemiological surveillance and carrying out health education activities.